E-Commerce Pada Masdokusnack.Id - Febby Nanda Utami; Masdiana (Journal of Applied Accounting And Business, 2022)
Masdokusnack.Id is one of the UMKM that sell snack and in promotions using brochures and sales that have to wait for the arrival of customers to place. Is there a problem that is a small promotion and requires a large cost, difficult to increase sales and explanation of product information is less clear. Therefore, this research aims to find PHP e-commerce system and MySQL database where the researcher develops system with waterfall method and uses unified model language model system approach using usecase diagram, activity diagram, class diagram and flow diagram diagram. The new system has input data ie admin data input, category data, product data, expedition data, sales input and output that generate customer data, product data, order data, data delivery of goods, payment data and forum data arranged to facilitate MASDOKUSNACK.ID in promotion and can increase sales with big amount, giving facility for member to order product, giving facility for employees to processing product data.